Mass and wind luminosity of young Galactic open clusters in Gaia DR2 - Celli, S.; Specovius, Andreas; Menchiari, S.; Mitchell, Alison; Morlino, G. (Astronomy & Astrophysics, 2024)
Context. Star clusters constitute a significant part of the stellar population in our Galaxy. The feedback processes they exert on the interstellar medium impact multiple physical processes from the chemical to the dynamical evolution of the Galaxy. In addition, young and massive stellar clusters might act as efficient particle accelerators and contribute to the production of cosmic rays. Aims. We aim at evaluating the wind luminosity driven by the young (< 30 Myr) Galactic open stellar clusters observed by the Gaia space mission. This is crucial for determining the energy channeled into accelerated particles. Methods. To do this, we developed a method relying on the number, magnitude, and line-of-sight extinction of the stars observed per cluster. Assuming that the stellar mass function follows a Kroupa mass distribution and accounting for the maximum stellar mass allowed by the age and mass of the parent cluster, we conservatively estimated the mass and wind luminosity of 387 local clusters within the second data release of Gaia. Results. We compared the results of our computation with recent estimates of young cluster masses. With respect to these, our sample is three times more abundant, particularly above a few thousand solar masses. This is of the utmost relevance for predicting the gamma-ray emission resulting from the interaction of accelerated particles. The cluster wind luminosity distribution we obtained extends up to 3 × 1038 erg s-1. This is a promising feature in terms of potential particle acceleration scenarios.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Mass function; Open clusters and associations: general; Outflows; Stars: luminosity function; Stars: mass-loss; Stars: winds